Sciatic neuroendometriosis: Magnetic resonance imaging defined perineural spread of endometriosis. Issue 7 (14th April 2016) - Cimsit, Canan; Yoldemir, Tevfik; Akpinar, Ihsan Nuri
Abstract: Catamenial sciatic radiculopathy resulting from endometriosis is a rare presentation of a common disease in which the pathogenesis of pain is still under debate. A 32‐year‐old woman presented complaining of infertility, catamenial sciatica, and pelvic and gluteal pain. Magnetic resonance imaging showed endometriotic infiltration of the left proximal lumbosacral plexus, sacral nerve track, sciatic nerve at the sciatic notch and pudendal nerve along the iliococcygeus muscle, together with left endometrioma and deep infiltrating endometriosis lesions. Laparoscopic endometriosis surgery was performed after all of the complications and possible outcomes of the surgery were discussed with the patient. Our case report highlights the importance of magnetic resonance imaging evidence of perineural spread, outlining the pathophysiology of the pelvic pain associated with neuroendometriosis.